Living Sunnah in Gayo Poetry Art: A Study of Abdurrahim Daudy’s Poems - Wazna, Ruhama; Arif, Muhammad (KARSA Journal of Social and Islamic Culture, 2022)
Religion and cultural customs coexist in the daily lives of Gayo people, including in the art of poetry. It is essential to know how Islamic values, as the religion of the majority of the population, play a role in shaping social behavior. This article aims to reveal the living sunnah side of Gayo poetry and how the traditions of the Prophet have been mentioned in a poem. The poetic works of Abdurrahim Daudy are the main focus of this paper. Since Daudy is a clerical and traditional figure in Gayo who has an artistic spirit in this modern era, it has become the main consideration why his poetic works are the focus of study in this paper. The data collection is done by library research and field research; namely, analyzing related literature, especially Daudy’s works, and conducting observations and interviews with several Gayo people. Using an anthropological approach and functionalism theory, all elements of culture are valuable parts of the society in which these elements are located. This study found that Syair, part of Gayo culture, has an essential role in shaping the behavior of the Gayo people themselves. However, in its development, the art of Gayo poetry has shifted in terms of lyrics and performance ethics which are increasingly superficial. However, the value of living the Prophet’s sunnah still seems to color Gayo’s poems, regardless of the motive of the person behind it, both as a poet and a listener.